A new species of Lynceus (Crustacea: Branchiopoda: Laevicaudata) from Patagonia, with comments on laevicaudatan systematics - Pessacq, Pablo; Epele, Luis B.; Rogers, D. Christopher (Zootaxa, 2011)
Lynceus mallinensis, a new species of laevicaudatan clam shrimp is described from a single temporary pool in Chubut province, Patagonia, Argentina. The form of the male rostrum necessitates a reevaluation of rostral characters for the genus. This species differs from L. rotundirostris, the only known Lynceus from Patagonia, by the absence of a distinct umbo. L. mallinensis is the fourth species of this genus and the fifth laevicaudatan to be reported from South America. The systematical position of the Laevicaudata is discussed in the Introduction.